Insecticides, Miticides & Molluscicides Available to Florida's Floricultural Industry: ENY-679/IN472, 1/2003 - Price, James F.; Nagle, Curtis; McCord, Jr., Elzie (EDIS, 2003)
This document is ENY-679, one of a series of the Entomology & Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: January 2003. https://edis.ifas.ufl.edu/in472